Perbedaan Penggunaan Media Video Animasi dan Kartu Bergambar terhadap Pencegahan Sexual Abuse pada Anak Usia Sekolah - Sri Tirtayanti; Fahmi Ristayani (Persatuan Perawat Nasional Indonesia Jawa Tengah, 2021)
The problem of sexual education is getting less attention from parents. Most parents think that sexual education is the responsibility of the school. Sex education that can be done to children is by using audiovisual media and picture cards. The purpose of this study was to determine the differences in the use of animated video media and picture cards on the prevention of sexual abuse in school-age children. This type of research is a quasi-experimental design with Two Group Design. The sample is students of SDN 5 Megang Sakti, totaling 30 students. The sampling technique used was purposive sampling. This study uses univariate and bivariate data analysis with dependent t test and independent sample t test. The results showed that the use of animated video media and picture cards had an effect on increasing knowledge of sexual abuse prevention in school-age children with value <0.05. Based on statistical tests, there are significant differences in the use of video media and picture cards with a value of value = 0.036. Both media are effective in increasing knowledge, but there is a difference of 2.3 between animated video media and picture cards which means that the use of animated video media is more effective than picture cards.